Characterization and potential biological control agent against white root rot pathogen (Rigidoporus microporus) in rubber tree (Hevea brasiliensis müll. arg.) - Go, Wen Ze (2019)
Rubber is the second most important commodity in Malaysia which grown primarily for the production of latex. Unfortunately, a major issue faced by majority of the rubber growing countries, including Malaysia is the devastating disease known as white root disease (WRD) caused by Rigidoporus microporus. This disease has been causing considerable latex yield loss and collapse of the mature rubber trees, consequently affecting its contribution to the economy of rubber producing countries. Thus, the search on using biological control agents (BCAs) against R. microporus in rubber tree has been focused in this study with locally isolated fungal species from the rhizosphere of healthy trees (HEA) and white root rot diseased trees (DIS). There were five different isolates of white root rot pathogen cultures, namely RL20, RL21, RL22, RL25 and RL26 were obtained from the Laboratory of Crop Improvement and Protection Unit, Rubber Research Institute of Malaysia (RRIM). All the pathogen isolates were subjected to morphological and molecular characterization for the species confirmation as R. microporus. Virulence among the pathogen isolates was determined in the pathogenicity test. Next, the soil samples collected from the rhizosphere of HEA and DIS were underwent serial dilution of 10^2 to 10^4 as to isolate the potential BCAs. The fungal isolation was performed on the potato dextrose agar Petri plates with species confirmation work was done by morphological and molecular identification. There were 35 fungal isolates that have been identified from both of the soils and their ability to inhibit the growth of R. microporus was screened in dual culture assay. Among these, there were four isolates from the genus of Trichoderma, i.e T. asperellum ST011, T. spirale HT009, T. koningiopsis HT001 and T. reesei ST013 have demonstrated greatest inhibition effect on the radial growth of R. microporus with majority achieved of > 75%. The ability of the Trichoderma isolates to serve as BCAs against R. microporus were further determined through the aspects of mycoparasitism, antibiosis, enzymatic and competition activities. The mycoparasitic activity of Trichoderma isolates has been revealed in the scanning electron microscopy (SEM). While antibiosis activities of Trichoderma isolates against R. microporus were tested in double plate and culture filtrate assays for their volatile and non-volatile effects. The natural compounds present in the secondary metabolites were further identified using the gas chromatography mass spectrometry (GC-MS) test, with some of the compounds were reported to have antimicrobial functions. The selected Trichoderma isolates have also revealed promising results on the production of chitinase, cellulase and glucanase enzymes in their respective qualitative and quantitative assays. Besides, they also possessed some plant growth-promoting activities to various degrees. Later, a scoring of antagonistic activity was done to select the best two performed fungal isolates in the biocontrol mechanisms as to test for their effectiveness against R. microporus in the nursery trial. The nursery trial was conducted through the preparation of biocontrol suspension in the concentration of 108 cfu/mL as to suppress the disease incidence caused by R. microporus. The percentage of efficacy was calculated based on the disease severity index of above and below grounds symptoms on each of the treatments. The present study demonstrated that the antagonists were able to boost in the soil and further compete with R. microporus whereby the single application of T. asperellum and the combination of both Trichoderma isolates were more promising. The disease suppression by BCAs were observed to have similar extend as of the chemical treatment which suggests that the selected Trichoderma isolates especially T. asperellum was a potential candidate for the biocontrol of R. microporus with its good persistence in the soil.